Knowledge, Attitude, and Behavior Regarding Homosexualilty among New Students in Universitas Padjadjaran - Ade Nea; Rudi Wisaksana; Enny Rohmawaty (Althea Medical Journal, 2018)
Background: Homosexualilty has raised a controversy in the society, which commonly has a negative attitude towards homosexual. It is important to develop knowledge and attitude about homosexuality in new students as agents of change. This study aimed to identify the knowledge, attitude, and behavior of new undergraduate students in Universitas Padjadjaran about homosexual.Methods: This was a descriptive quantitative cross-sectional study using primary data obtained from questionnaires, distributed not randomly to new undergraduate students of 2016/2017 academic year in Universitas Padjadjaran (n=122) from October to November 2016. Questions asked were demographic data, knowledge and attitude towards homosexualilty, and homosexual behavior.Results: Respondents had a good knowledge (18%; n=22), average (66.4%; n=81) and low knowledge (15.6%; n=19) about homosexuality and the majority (55.7%; n=68) of respondents had a negative attitude towards homosexuality. A heterosexual behavior had been showed in 92.6% (n=113) respondents, and 7.4% (n=9) had a heterosexual dominant behavior.Conclusions: In our new undergraduate students’ community, the majority has average knowledge, however, with a negative attitude towards about homosexuality. The role of new students as agents of change is to educate the community to prevent potential health issues. The developing of knowledge, attitude, and behavior towards homosexual through a holistic education from health workers should be promoted.